The Role of Videos and Simulators in the Professional Communicative Training of Future Technical Specialists in Russian Language Classes - Kayumov Bakhtiyar Ishbaevich (Genius Publishing Group, 2025)
This article examines issues of pedagogical activity, the use of innovative technologies in the teaching process, and the role of visual methods in developing professional competence.
Keywords: teacher; pedagogical activity; educational content; visual methods